2017
DOI: 10.4172/2327-5073.1000273
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Piperacillin/Tazobactam and Ticarcillin/Clavulanate Susceptibilities in Pseudomonas aeruginosa Isolates in Hospitalised Patients by E-test Gradient Method and Comparison of Results with Disk Diffusion Tests

Abstract: Pseudomonas aeruginosa is an important opportunistic pathogen in human infections. P. aeruginosa is naturally resistant to many antibiotics and mutations can result in resistance development during treatment as well. Piperacillin/tazobactam and Ticarcillin/clavulanate are β-lactam/β-lactamase inhibitor combination with a wide spectrum of antibacterial activity. In this study was aimed to determine the susceptibility of P. aeruginosa isolates to Piperacillin/tazobactam and Ticarcillin/clavulanate antibiotics by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The lowest antibiotic resistance rates in biofilm-positive and biofilm-negative isolates were seen against piperacillin/tazobactam (34.3 and 15.4%, respectively). This result agrees with Namuq et al [ 29 ] who reported piperacillin/tazobactam resistance (5%), Hoque et al [ 30 ] who reported (3.37%), and Direkel et al [ 31 ] who reported (7%). Also, in a study performed by Delissalde and Amábile-Cuevas, the resistance of biofilm-producing strains against piperacillin/tazobactam was 35%, which was very similar to our results [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The lowest antibiotic resistance rates in biofilm-positive and biofilm-negative isolates were seen against piperacillin/tazobactam (34.3 and 15.4%, respectively). This result agrees with Namuq et al [ 29 ] who reported piperacillin/tazobactam resistance (5%), Hoque et al [ 30 ] who reported (3.37%), and Direkel et al [ 31 ] who reported (7%). Also, in a study performed by Delissalde and Amábile-Cuevas, the resistance of biofilm-producing strains against piperacillin/tazobactam was 35%, which was very similar to our results [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…P. aeruginosa (PA1) was resistant to piperacillin, piperacillin/tazobactam, meropenem and ceftazidime. Piperacillin, cefotaxime and ceftazidime resistant E.coli isolates and piperacillin/tazobactam, meropenem and ceftazidime resistant P. aeruginosa isolates have been reported in previos studies (Tavío et al, 2014;Hunter et al, 2010;Akova, 2016;Andersen et al, 2005;Direkel et al, 2017;Mirsalehian et al, 2017;Rostami et al, 2018;Kos et al, 2016). These isolates restricts treatment options and cause problems in clinical settings.…”
Section: Resarch Findingsmentioning
confidence: 99%
“…In a study conducted in our country, it has been reported that piperacillin-tazobactam and amikacin are the most effective antibiotics against P. aeruginosa isolates. However, piperacillintazobactam resistance rates in P. aeruginosa isolates increased between 2007 and 2015 (Direkel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The antibiotic penetration from the strip into the medium containing agar caused an oval zone. Moreover, the MIC was decided to be the point where the oval zone crossed the strip (21,22).…”
Section: Resultsmentioning
confidence: 99%